Selenium level in steroid-resistant and steroid-sensitive nephrotic syndrome - Sudung Oloan Pardede; Andini Striratnaputri; Muzal Kadim (Indonesian Pediatric Society, 2020)
Background The mechanisms of pathogenesis of steroid-resistant nephrotic syndrome (SRNS) and steroid-sensitive nephrotic syndrome (SSNS) are not well understood. Antioxidants, such as glutathione peroxidase enzyme (GPx) and its cofactor, selenium, are thought to slow the progress of nephrotic syndrome (NS). Objective To compare selenium levels in SRNS and SSNS pediatric patients. Methods This cross-sectional study was conducted in 51 SRNS and 30 SSNS patients, aged 2 to 18 years, who visited the Pediatric Nephrology Outpatient Clinic at Cipto Mangunkusumo Hospital, Jakarta. Subjects were included by consecutive sampling. Selenium was measured on venous blood using GC tools MS â„¢ (Agilent technologies, inc.). Results Median selenium levels in SRNS patients were 92 (range 42-154) Î¼g/L and in SSNS patients were 93 (range 69-193) Î¼g/L. Conclusion Selenium levels in SRNS and SSNS patients were not significantly different.